The Candidate as a “Political Goods” and the Electorate as a “Potential Client”: The Role of Public Relation on Political Campaign - Magda Kotrikazdze (Indonesian Journal of Cultural and Community Development, 2023)
The article is being concentrated on the essence of political PR and its components. Distinction within the directions of political PR will be made between PR of the public branches and electoral campaign PR. We will discuss the role and important of PR tools, also inform you about PR as a discipline and its background and its importance as in domestic as well in foreign political developments. We will focus on a PR as a mediator between media, politics and public, the PR professional as a practical implementer of PR, also PR profession in itself, fundamental principles of ethics, ethical PR, as its major driving vector. Media, as marketing instument, also marketing as one of the most powerful tool for managing political campaigns and, of course, their interconnection and collaboration with the issues of political PR and security.